The National Emergency Access Target (NEAT): can quality go with timeliness?. Issue 3 (18th February 2013) - Maumill, Liana; Zic, Mia; Esson, Amanda A; Geelhoed, Gary C; Borland, Meredith M; Johnson, Christopher; Aylward, Philip; Martin, Andrew C
Abstract: Objective: To report the experience of implementing a 4‐hour‐rule program. Design, setting and participants: A 3‐year whole‐of‐hospital clinical service redesign program in a tertiary paediatric hospital in Western Australia, involving all patients presenting to the emergency department (ED) from 1 January 2009 to 31 December 2011. Main outcome measures: Percentage of patients admitted, discharged or transferred from the ED within 4 hours of arrival at triage, and percentage of patients discharged from inpatient wards before 10 am. Results: The percentage of patients admitted, discharged or transferred within 4 hours of arrival at the ED increased from 87% in 2009 to 95% in 2011. Safety and quality measures, including the admission rate from the ED, unplanned reattendances at the ED within 48 hours of discharge, patient complaints and inhospital mortality, remained unchanged. The percentage of patients discharged from inpatient wards before 10 am increased from 18% in 2009 to 30% in 2011. Conclusions: The introduction of a 4‐hour‐rule program has resulted in improved timeliness of care for patients throughout the hospital, both in the ED and inpatient wards, with no adverse impact on the quality and safety of clinical care.